2015
DOI: 10.1021/ac504151e
|View full text |Cite
|
Sign up to set email alerts
|

Nanopipet-Based Liquid–Liquid Interface Probes for the Electrochemical Detection of Acetylcholine, Tryptamine, and Serotonin via Ionic Transfer

Abstract: A nanoscale interface between two immiscible electrolyte solutions (ITIES) provides a unique analytical platform for the detection of ionic species of biological interest such as neurotransmitters and neuromodulators, especially those that are otherwise difficult to detect directly on a carbon electrode without electrode modification. We report the detection of acetylcholine, serotonin, and tryptamine on nanopipet electrode probes with sizes ranging from a radius of ≈7 to 35 nm. The transfer of these analytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
102
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(111 citation statements)
references
References 59 publications
4
102
0
Order By: Relevance
“…21,29,30 Briefly, the diffusion limited steady state current at nanoITIES pipet electrodes can be expressed as 35 i=4italicxnFDcawhere i is the steady-state current, x is a function of the quantity RG = r g / a ( r g and a are outer and inner tip radii, respectively), 35 n is the number of transferred charges, F is Faraday’s constant, a is the radius of the electrode, D is the diffusion coefficient of the neurotransmitter, and c is the concentration of the neurotransmitter. A proposed disk geometry for the nanopipet tip was used for the calculation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…21,29,30 Briefly, the diffusion limited steady state current at nanoITIES pipet electrodes can be expressed as 35 i=4italicxnFDcawhere i is the steady-state current, x is a function of the quantity RG = r g / a ( r g and a are outer and inner tip radii, respectively), 35 n is the number of transferred charges, F is Faraday’s constant, a is the radius of the electrode, D is the diffusion coefficient of the neurotransmitter, and c is the concentration of the neurotransmitter. A proposed disk geometry for the nanopipet tip was used for the calculation.…”
Section: Methodsmentioning
confidence: 99%
“…The current values from three replicate background CVs at the diffusion limited potential of GABA transfer were used to calculate the standard deviation of the background, as done in our previous study. 29,30 …”
Section: Methodsmentioning
confidence: 99%
“…After that, the pipettes were back-filled with a filling solution of 5 mM TDDATFAB + 1 mM DB 18 C 6 dissolved in DCE. The filling solution was chosen based on what was available/already prepared at the time of the experiments, however, a solution with just 5 mM TDDATFAB and without DB 18 C 6 would also work for ACh detection as shown in our recent work 39 as ionophore is not needed for ACh detection. A platinum wire was inserted into the pipette and fixed with wax.…”
Section: Methodsmentioning
confidence: 99%
“…The cationic form of tryptophan transferring across NB−water interface was also studied using an acidic aqueous solution. Colombo et al [98] reported the detection of acetylcholine, serotonin and tryptamine on the nano-ITIES formed at nanopipettes with sizes ranging from a radius of ca. 7 nm to 35 nm, using CV and amperometry.…”
Section: Facilitated Ion-transfer (Fit) Reactionsmentioning
confidence: 99%